Pengaruh Cetakan Terhadap Hasil Kericu Pada Mesin Pembuat Kericu - Irawan, Terris; Wahyudie, Illham Ary; Husman, Husman (Manutech : Jurnal Teknologi Manufaktur, 2025)
The Bangka Belitung Islands consist of two main islands, namely Bangka Island and Belitung Island, which have abundant marine natural resource potential. One of the typical products of the seafood is Kericu, which is a snack made from squid eggs and sago. Kericu has become a special souvenir that is in demand and has become a home-based business opportunity. UMKM "Ampiang Yu Erin" is one of the producers of keriku whose manufacture is still using manual methods, which causes obstacles in terms of worker fatigue and product inconsistencies. To overcome this problem, modifications to the crevice forming machine are carried out to improve production efficiency and product uniformity. Although the desired results have not yet been fully achieved, the trial showed progress close to the expected crease shape, confirming the importance of the mold in influencing the final quality of the product. The Bangka Belitung Islands consist of two main islands, namely Bangka Island and Belitung Island, which have abundant marine natural resource potential. One of the typical products of the seafood is Kericu, which is a snack made from squid eggs and sago. Kericu has become a special souvenir that is in demand and has become a home-based business opportunity. UMKM "Ampiang Yu Erin" is one of the producers of keriku whose manufacture is still using manual methods, which causes obstacles in terms of worker fatigue and product inconsistencies. To overcome this problem, modifications to the crevice forming machine are carried out to improve production efficiency and product uniformity. Although the desired results have not yet been fully achieved, the trial showed progress close to the expected crease shape, confirming the importance of the mold in influencing the final quality of the product.